1974
DOI: 10.1139/v74-559
|View full text |Cite
|
Sign up to set email alerts
|

Comments on the Crystal Structure of Polypivalolactone and Deviation of Ester Groups from trans Planarity

Abstract: (1974).The crystalline conformation of polypivalolactone was determined by analysis of the chain conformational energies and it was found that the minimum energy corresponds to a planar tmrzs conformation for the ester group. The result was con~pared to published X-ray data based on fiber diffraction which show a significant deviation from trans planarity. This difference is discussed in terms of the relative energies involved and by comparison with literature crystallographic results of low molecular weight c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
59
0

Year Published

1977
1977
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 8 publications
1
59
0
Order By: Relevance
“…They correspond, via Bragg's equation, to measures of 0.88 nm > d > 0.44 nm, larger than interatomic distances, but matching interchain distances in iso-PHB. 23 The average interchain distances in amorphous PHB can be expected to be of the same order; oscillations around which determine the broadness of the amorphous pattern. 27 Because of the lack of long-range order, no higher-angle diffraction intensities, which would result from higher Miller index lattice planes, are observed.…”
Section: Macromoleculesmentioning
confidence: 99%
“…They correspond, via Bragg's equation, to measures of 0.88 nm > d > 0.44 nm, larger than interatomic distances, but matching interchain distances in iso-PHB. 23 The average interchain distances in amorphous PHB can be expected to be of the same order; oscillations around which determine the broadness of the amorphous pattern. 27 Because of the lack of long-range order, no higher-angle diffraction intensities, which would result from higher Miller index lattice planes, are observed.…”
Section: Macromoleculesmentioning
confidence: 99%
“…1(a)shows the chemical structure of PHB, which has been determined by the wide-angle x-ray diffraction measurement [50]. It was reported that the unit cells of PHB belong to the orthorhombic system, P2 1 2 1 2 1 (D 2 4), (α = β = γ =90 o ) with a=5.76 Å, b=13.20 Å, c=5.96 Å (fiber repeat) [50,51]. In our system we have considered super cell (a×4, b×2, and c×4) keeping the same lattice parameter.…”
Section: Resultsmentioning
confidence: 99%
“…It seeins well established that the barr~er to rotatlon around the former 1s very high and that only small departures from planarity of the ester group are poss~ble (7,8). The conformat~on around the C(6)-O(6) bond can be rat~onal~zed on the basls of non-bonded and electrostat~c Interact~ons alone.…”
Section: Introductionmentioning
confidence: 98%